A CRITICAL DISCOURSE ANALYSIS OF BTSâ€™ SONG â€œONâ€ (SYSTEMIC FUNCTIONAL LINGUISTICS APPROACH) - Sulistyawati, Hefy; Krisifu, Adolfina; Sumarlam (Center of Language and Cultural Studies [CLCS], 2022)
Song is a type of transactional discourse which contains a singer’s message or ideology to be delivered to their fans or general public about certain issues, either related to personal or social ones. The ideology and the relative power of a song can be analyzed through linguistic perspective using Critical Discourse Analysis (CDA) approach by investigating its discourse meaning and its relevance to the surrounding social and cultural context. This is a descriptive qualitative study which aims at revealing the ideology of acceptance, self-love and self-perseverance of the song ON by BTS through Halliday’s (2004) Systemic Functional Linguistics and Fairclough’s (1995) concept of CDA by analyzing the transitivity, mood types and metaphors. The followings are the results namely i) the transitivity comprises 46 material process, 8 mental process, 16 relational process, 3 behavioral process and 2 verbal process; 2) the mood system consists of 47 indicative declarative, 3 indicative interogative and 25 imperatives; and 3) there are 5 metaphors found in the song. In a nut shell, this song delivers an important message of accepting and loving their true selves, self-reliance and perseverance towards prejudice and bullying from others, as well as confidence towards any challenges ahead.